SlGRAS4 accelerates fruit ripening by regulating ethylene biosynthesis genes and SlMADS1 in tomato. (1st January 2021) - Liu, Yudong; Shi, Yuan; Su, Deding; Lu, Wang; Li, Zhengguo
Abstract: GRAS proteins are plant-specific transcription factors that play crucial roles in plant development and stress responses. However, their involvement in the ripening of economically important fruits and their transcriptional regulatory mechanisms remain largely unclear. Here, we demonstrated that SlGRAS4, encoding a transcription factor of the GRAS family, was induced by the tomato ripening process and regulated by ethylene. Overexpression of SlGRAS4 accelerated fruit ripening, increased the total carotenoid content and increased PSY1 expression in SlGRAS4 -OE fruit compared to wild-type fruit. The expression levels of key ethylene biosynthesis genes ( SlACS2, SlACS4, SlACO1, and SlACO3 ) and crucial ripening regulators ( RIN and NOR ) were increased in SlGRAS4 -OE fruit. The negative regulator of tomato fruit ripening, SlMADS1, was repressed in OE fruit. Exogenous ethylene and 1-MCP treatment revealed that more endogenous ethylene was derived in SlGRAS4 -OE fruit. More obvious phenotypes were observed in OE seedlings after ACC treatment. Yeast one-hybrid and dual-luciferase assays confirmed that SlGRAS4 can directly bind SlACO1 and SlACO3 promoters to activate their transcription, and SlGRAS4 can also directly repress SlMADS1 expression. Our study identified that SlGRAS4 acts as a new regulator of fruit ripening by regulating ethylene biosynthesis genes in a direct manner. This provides new knowledge of GRAS transcription factors involved in regulating fruit ripening.